Zarządzanie wiedzą multimedialną w środowisku nauczania na odległość - Hauke, Krzysztof (Management knowledge multimedia in environment distance learning, 2005)
The article presents a management knowledge multimedia in system e-leaming. The term multimedia describes a number of diverse technologies that allow visual and audio media to be combined in new ways for the purpose of communicating. Applications include entertainment, education and advertising. Multimedia often refers to computer technologies. Nearly every PC built today is capable of multimedia because they include a CD-ROM or DVD drive, and a good sound and video card (often built into the motherboard). But the term multimedia also describes a number of dedicated media appliances, such as digital video recorders (DVRs), interactive television, MP3 players, advanced wireless devices and public video displays. http://www.scala.com/multimedia/multimedia-defmition.html - data dostępności 21.12.2004 Knowledge management is the collection of processes that govern the creation, dissemination, and utilization of knowledge. In one form or another, knowledge management has been around for a very long time. Practitioners have included philosophers, priests, teachers, politicians, scribes, liberians, etc. Distance learning environments supported by local area networks and the internet provide new channels for collaborative models of learning, training, teaching, and ultimately the construction of knowledge. Multimedia browsing and authoring, desktop video conferencing, and specialized animations, simulations, and games provide new media for learning. As the infrastructure for this environment unfolds, the question is how to use it in new effective ways to support not only current models of education but new methods of student student, student-educator, and educator-educator collaboration in the learning process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 67-79